Meningkatkan Efektivitas Penilaian Karyawan Di Bawaslu Jakarta Barat Dengan Sistem Pendukung Keputusan Berbasis Analytical Hierarchy Process - Wulandari, Lita Eka; Sutrisno , Tri; Lewenusa, Irvan (CV. Information Technology Training Center - Indonesia (ITTC), 2025)
Employees are an important resource in a company or agency, including the West Jakarta City Bawaslu, which routinely assesses the performance of its employees. This assessment is often time consuming and prone to human error, given that the process is still carried out manually. For this reason, this research aims to design a web-based Decision Support System (SPK) using the Analytical Hierarchy Process (AHP) method that can assist Bawaslu in determining the best employees more efficiently and accurately. The AHP method is used because it is able to break down complex problems into simpler and more structured ones, and provides a measurement scale that can be used to determine priorities in selecting the best employees. Research data was collected through interviews with the leadership of the West Jakarta Bawaslu and literature studies related to the AHP method. The results of this study are expected to facilitate decision making in selecting the best employees and improve the efficiency of the performance appraisal process at the West Jakarta Bawaslu.